1586. Prevalence and Significance of Pre-transplant BK Viremia and Viruria in Deceased and Living Kidney Donors and Kidney Transplant Recipients. (26th November 2018) - Tan, Susanna K; Sahoo, Malaya K; Huang, ChunHong; Weber, Jenna; Kurzer, Jason; Concepcion, Waldo; Chin-Hong, Peter; Subramanian, Aruna; Tan, Jane; Pinksy, Benjamin
Abstract: Background: BK virus (BKV) is a major cause of nephropathy in kidney transplantation. Pre-transplant BKV shedding in the donor or recipient may increase the risk for developing BKV viremia in kidney transplant recipients. Methods: From August 2016 to December 2017, we prospectively performed pre-transplant BKV DNA PCR testing on plasma and urine samples from deceased kidney donors procured through Donor Network West, our local organ procurement organization and third largest in the country. We also simultaneously performed pre-transplant BKV DNA PCR testing of plasma and urine from living kidney donors and adult kidney transplant recipients as well as post-transplant surveillance testing of recipients at Stanford University Medical Center. Results: BKV DNA PCR testing of plasma and urine samples from 212 deceased kidney donors revealed 17 donors that were positive (16 in urine, 1 in plasma; 8.02% BKV DNA detection). Fifty of these specimens went to Stanford kidney transplant recipients, including four donors with BKV viruria (8.00%). During the study period, we obtained complete pre-transplant donor and recipient pairings for 47 deceased and 39 living adult kidney transplant recipients. Of these 86 kidney recipients, none had detectable BKV DNA in pre-transplant donor or recipient plasma specimens, while 10 (four deceased, six living) had BKV DNA detected in the urine. The majority (9/10) were positive in the donor urine, with one positive in the recipient and one in both the recipient and donor. After a minimum follow-up of 5 months, three (30%) had developed BKV viremia, compared with three of the 76 (3.9%, P = 0.009) with negative pre-transplant BKV DNA. The rate of BKV viruria was not significantly different between deceased and living kidney donors (4/47 (8.5%) vs. 6/39 (15.4%), P = 0.32). Conclusion: In one of the largest cohorts in the United States that also includes deceased donor testing, we demonstrate that pre-transplant BKV viruria, particularly of the donor, is associated with development of BKV viremia in kidney transplant recipients. Pre-transplant BKV DNA screening in the urine of kidney donors (deceased and living) may be useful in predicting risk for BKV viremia. Disclosures: All authors: No reported disclosures.